Making the Case for Uniformity in Professional State Licensure Requirements - Janice A. Brannon; Ellen R. Cohn; Jana Cason (International Journal of Telerehabilitation)
Telehealth, the use of communication and information technologies to deliver health services, was initially envisioned as a way for persons in rural or remote settings to receive otherwise unavailable healthcare services. Now, in addition to overcoming personnel shortages for underserved populations, telehealth shows promise in meeting the needs of a constantly mobile U.S. society and workforce.  Fortunately, telerehabilitation can meet the needs of a mobile society and workforce by enabling continuity of care for individuals who are out-of-town, on vacation, in temporary residence as a university student, or on business travel. Unfortunately, outdated legislative and regulatory policies and inhospitable infrastructures currently stand in the way of a seamless continuum of care. In 2010, the American Telemedicine Association’s Telerehabilitation Special Interest Group (TR SIG) convened a License Portability Sub-Committee to explore ways to diminish barriers for state licensure portability with a particular focus on physical therapy, occupational therapy, speech therapy, and audiology.  In 2011, the Subcommittee published a factsheet that detailed the challenges and potential solutions that surround the difficult issue of licensure portability.  Concurrently, the American Telemedicine Association is advocating for national reform of professional licensure. At the heart of all licensure requirements is the ability to determine who should be granted the authority to practice in a particular profession.  This is done by focusing on educational, examination and behavioral requirements that are deemed the minimum necessary to protect the public from harm.  States, however, with whom authority for licensure of health professionals rests, have independently determined those minimum requirements.  This approach has led to a myriad of requirements that vary from state to state.  Licensure portability will best succeed when variability between licensure requirements is minimized and an efficient licensure process exists.    In this paper, these two critical factors for licensure portability are referred to as “licensure requirements” and “the credentialing process.”  Currently the variability between both of these factors is different between professions as well as between jurisdictions.   To find the best solution to licensure portability, it is critical to determine which of these two elements create significant barriers for licensure mobility. This document outlines a method for the professions to begin collecting data to pinpoint the areas where agreement and variations exist in licensure requirements and processes between states.  Such information will inform efforts towards uniformity.